Inhibitory and inductive effects of Corydalis saxicola Bunting total alkaloids (CSBTA) on cytochrome P450s in rats. (28th May 2018) - Yu, Jiaojiao; Liu, Qiuyan; Lu, Xiaoyu; Li, Xiaonan; Li, Ning; Liu, Baolin; Huang, Fang; Qiu, Zhixia
Abstract : Corydalis saxicola Bunting, a well‐known traditional Chinese medicine in south China, has been widely used for the treatment of various hepatic diseases. Its active ingredients are Corydalis saxicola Bunting total alkaloids (CSBTA), which primarily include dehydrocavidine, palmatine, and berberine. These representative alkaloids could be metabolized by hepatic CYP450s. Hence, it is necessary to investigate the potential influences of CSBTA on CYP450s to explore the possibility of herb–drug interactions. In present study, in vitro inhibition and in vivo induction studies were performed to evaluate the potential effects of CSBTA extract on CYP450s in rats. Inhibition assay illustrated that CSBTA exerted inhibitory effects on CYP1A2 (IC50, 38.08 μg/ml; Ki, 14.3 μg/ml), CYP2D1 (IC50, 20.89 μg/ml; Ki, 9.34 μg/ml), CYP2C6/11 (IC50 for diclofenac and S‐mephenytoin, 56.98 and 31.59 μg/ml; Ki, 39.0 and 23.8 μg/ml), and CYP2B1 (IC50, 48.49 μg/ml; Ki, 36.3 μg/ml) in a noncompetitive manner. Induction study showed CSBTA had obvious inhibitory rather than inductive effects on CYP1A2 and CYP2C6/11. Interestingly, neither inhibition nor induction on CYP3A was observed for CSBTA. In conclusion, CSBTA–drug interactions might occur through CYP450s inhibition, particularly CYP1A and CYP2D. Further studies are still needed to elucidate the underlying mechanisms of inhibition.